Dendritic excitations govern back-propagation via a spike-rate accelerometer - Pojeong Park; J. David Wong-Campos; Daniel G. Itkis; Byung Hun Lee; Yitong Qi; Hunter C. Davis; Benjamin Antin; Amol Pasarkar; Jonathan B. Grimm; Sarah E. Plutkis; Katie L. Holland; Liam Paninski; et al. (Nature Communications)
Abstract Dendrites on neurons support electrical excitations, but the computational significance of these events is not well understood. We developed molecular, optical, and computational tools for all-optical electrophysiology in dendrites. We mapped sub-millisecond voltage dynamics throughout the dendritic trees of CA1 pyramidal neurons under diverse optogenetic and synaptic stimulus patterns, in acute brain slices. Our data show history-dependent spike back-propagation in distal dendrites, driven by locally generated Na+ spikes (dSpikes). Dendritic depolarization created a transient window for dSpike propagation, opened by A-type KV channel inactivation, and closed by slow NaV inactivation. Collisions of dSpikes with synaptic inputs triggered calcium channel and N-methyl-D-aspartate receptor (NMDAR)-dependent dendritic plateau potentials and accompanying complex spikes at the soma. This hierarchical ion channel network acts as a spike-rate accelerometer, providing an intuitive picture connecting dendritic biophysics to associative plasticity rules.